Effect of Wind to the Maneuvering Ship Control in the Avoidence Collision - I. G. A. N. M. Pratama Putra (IPTEK The Journal for Technology and Science, 2012)
Marine transportation as an important roles in Indonesia, it is two third of Indonesian territorial is waters. Tanjung Perak port is one busiest transportation in Indonesia. To enter the terminal ship is shipping throuh Madura strait. To enhance ship safety management, navigational device known as AIS used for navigational purpose. AIS data contain multiple ship specification, statically and dynamically. Those data can be used as inputs in maneuvering control. This research focus on creating ship maneuvering control system by utilizing AIS data. The strategic control is Fuzzy Logic (FL). The aim of research is carrying ship to the trajectory to collision avoidence to other ship. The Fuzzy Logic Control consits two units: Heading control and speed control. The case study is applying controler to the cargo ship, and disturbance is wind in various coming angle.